Весь-человек Михаилa Пришвинa (на материале повести „Корабельная чаща”) - Szubin, Roman (Studia Rossica Posnaniensia, 2019)
Article is devoted to studying a concept of all-unity, all-man (rus. всеединство, всечеловек) in the story The Ship Forest (Korabel’naya Chashcha) of the Russian writer Mikhail Prishvin. The idea of all-unity, of unity common to all mankind, peculiar to the Russian thought, has found expression in a symbol All-man (Весь-человек). The image-symbol is considered through a number of collective forms and personalities, its language form, conceptual filling, development of an image in the case of diaries of Prishvin is investigated. The author focuses on the problem of sectarianism in the Russian culture and radicalization of collective life at the beginning of the 20th century in the Bolshevism. As a method hermeneutical developments of Vardan Hayrapetyan in the field of the Russian folklore are applied. The symbol of the All-man corresponds to a mytheme of a first-man and with hermeneum the man of the world (the world person), embodying the archaic idea of rescue.